Lower Glycated Hemoglobin with Real-Time Continuous Glucose Monitoring Than with Intermittently Scanned Continuous Glucose Monitoring After 1 Year: The CORRIDA LIFE Study - Radovnická, Lucie; Hásková, Aneta; Do, Quoc Dat; Horová, Eva; Navrátilová, Vendula; Mikeš, Ondřej; Cihlář, David; Parkin, Christopher G; Grunberger, George; Prázný, Martin; Šoupal, Jan (Diabetes technology & therapeutics, 2022)
Background: The aim was to compare the efficacy of real-time continuous glucose monitoring (rtCGM) and intermittently scanned continuous glucose monitoring (isCGM) focusing on glycated hemoglobin (HbA1c) as the primary endpoint. Methods: The CORRIDA LIFE was a 12-month, real-world, nonrandomized study that is part of the CORRIDA clinical trials program. The study compared rtCGM (Dexcom G5 or G6) and isCGM (FreeStyle Libre 14-Day; Abbott) in adults with type 1 diabetes (T1D). Only patients on multiple daily insulin injections or continuous subcutaneous insulin infusion with no automatic functions were included in this study. Primary outcome was the difference in HbA1c between study groups at 12 months. Results: One hundred ninety-one adults with T1D (mean age 40 ± 13 years, HbA1c 8.1% ± 3.4% [65 ± 14 mmol/mol]) participated in this study; 81 patients initiated rtCGM and 110 initiated isCGM. After 12-months, HbA1c was significantly lower with rtCGM versus isCGM (7.1% ± 3.1% [54.1 ± 10.1 mmol/mol] vs. 7.7% ± 3.3% [61.2 ± 12.2 mmol/mol]), P = 0.0001. The percentage of time in hypoglycemia (<70 mg/dL [<3.9 mmol/L]) was lower among rtCGM vs. isCGM participants [4.3% ± 2.8% vs. 6.4% ± 5.3%], P = 0.003). Patients with rtCGM spent less time in clinically significant hypoglycemia (<54 mg/dL [<3.0 mmol/L]) (0.9% ± 1.0% vs. 2.3% ± 2.5%, P < 0.0001) and more time in target range (70-180 mg/dL [3.9-10 mmol/L]) than isCGM users (67.5% ± 14.8% vs. 57.8% ± 17.0%), P = 0.0002. Conclusions: rtCGM was superior to isCGM in HbA1c, hypoglycemia, and other glycemic outcomes. Our findings provide guidance to clinicians when discussing monitoring options with their patients. The study was registered at www.clinicaltrials.gov (NCT04759495).
Keywords: dospělí; Flash glucose monitoring; hypoglykemie; Continuous subcutaneous insulin infusion; Time in range; Continuous glucose monitoring; Adult; lidé; Blood Glucose; Type 1 diabetes; Hypoglycemic Agents; Insulin; Glycated Hemoglobin A; Diabetes Mellitus, Type 1; hypoglykemika; selfmonitoring glykemie; Multiple daily insulin injections; glykovaný hemoglobin; lidé středního věku; inzulin; krevní glukóza; Glycated Hemoglobin; Middle Aged; Blood Glucose Self-Monitoring; diabetes mellitus 1. typu; Glycated hemoglobin; Hypoglycemia; Humans